Repercussões morfofuncionais da remobilização com mobilização articular passiva e ultrassom terapêutico no músculo sóleo de ratos Wistar - Chico, Fernanda Teixeira Furlan (2023)
Immobilization commonly happens in the treatment of musculoskeletal injuries or prolonged rest, such as patients who remain bedridden in hospital environments for a long time, leading to important morphofunctional changes, such as muscle atrophy, tissue disorganization, increase in inflammatory cells, decrease in strength and functionality. Therefore, methods that accelerate rehabilitation are extremely valuable, such as therapeutic ultrasound and passive mobilization, which can be used in remobilization. The objective of this study was to analyze these treatments in an isolated and associated way, in the recovery of the soleus muscle of immobilized Wistar rats. Forty rats, aged approximately 10 weeks, were randomly allocated into 5 groups (n=8), GI (immobilization), GRL (free remobilization), GRMP (remobilization with passive mobilization), GRU (remobilization with therapeutic ultrasound) and GRMU (remobilization with passive mobilization and therapeutic ultrasound). The animals were immobilized with plaster bandage on the right pelvic limb for 21 days and sequentially distributed according to the treatment (for 3 weeks). The experimental phase of GI was completed after 21 days of immobilization, the GRL continued with free movement, the GRMP had the passive mobilization treatment (being grade IV of joint mobilization, with approximately 50 movements in 1 minute), the GRU was treated with ultrasound (frequency of 1.0 MHz, intensity of 0.5 w/cm2 for 2 minutes on the knee and ankle and the GRMU had the association of the two therapeutic techniques. The animals were functionally evaluated with the Von Frey and strength tests grip, before immobilization, after immobilization and once a week during the treatment phase, totaling 5 evaluations. After collecting the soleus muscle, processing was performed for analysis of general morphology, using hematoxylin-eosin staining, Masson's trichometer for analysis of connective tissue and muscle spindles, in addition to the histopathological index for level of tissue injury. Statistical data were analyzed using SPSS 20.0 ® software using models generalized linear (p < 0.05) As for the functional results, all groups showed a lower nociceptive threshold after the removal of the orthosis and the GRMU showed better recovery in relation to muscle strength. The morphology of the soleus muscle of the immobilized animals showed atrophy and necrosis of the muscle fibers, an increase in inflammatory cells, disorganization and an increase in the connective tissue, confirmed by the histopathological index, while the GRU presented a greater number of capillaries and congested blood vessels. Regarding the tissue organization, the GRMU presented a smaller amount of connective tissue, and with greater organization. As for the neuromuscular spindles, the GRL and the GRMU showed greater capsule thickening. Therefore, immobilization affects functionality and causes severe tissue damage. Both proposed treatments improved functional assessments and morphology, however, the associated techniques enhanced tissue recovery.